An investigation of red gypsum as replacement material to improve the performance of grounding system - Nur Farahana, Yusri (2019)
Earth grounding system serves as lightning-protection in industrial and power plants. One of the major parameters to determine the performance of the grounding system is the resistivity of local soil. Natural occurring or manufactured Gypsum, a soft white or grey mineral consists of hydrated calcium sulphate is used as ground enhancement material. The gypsum content was found to improve the electrical conductivity of materials. On the other hand, red gypsum (RG) is a waste generated from a sulphate process of ilmenite ore to acquire titanium dioxide. Due to the gypsum content in both material are similar it is expected that red gypsum can be an alternative to white gypsum. In this study, RG was tested and compared with white gypsum to perform a grounding material. The geotechnical properties such as physical and chemical properties were tested first, followed by establishing soil-water retention curve and determination of the resistivity behaviour. A chilled-mirror dew-point and osmotic techniques were used to establish SWRC whereas a 2-point resistivity meter and soil box attachment were used to measure the resistivity of both gypsum and RG under different condition. Test results showed that, the geotechnical properties of RG is different to that of white gypsum. The RG absorbed more water and has higher plasticity characteristic as compared to common gypsum. The resistivity of gypsum and RG are 8 Ω.m and 11 Ω.m, respectively indicating that gypsum is slightly better grounding material than RG, however the differences was found to be very small.